Use of rivaroxaban and acetylsalicylic acid as a combined treatment for peripheral arterial disease in Central Military Hospital - Román-Hernández, Rigoberto; Banegas-Ruiz, Rodrigo; Jiménez-Nateras, Claudia N.; Martínez-Meraz, Manuel; Torres-Alarcón, Carmen G.; Espejel-Blancas, José A.; Colón, José Á. B.; Caprielova, Yuri J.; Llergo, Román A. R.; Torres, Juan P. E.; Mendoza-Barrera, German E.; Valderrama-Treviño, Alan I.; et al. (International Journal of Research in Medical Sciences, 2020)
Background: The objective of this research was to evaluate the behavior of 3 risk indicators for peripheral arterial disease in patients under oral treatment with rivaroxaban 2.5 mg every 12 hours plus, acetylsalicylic acid 100 mg every 24 hours. It was hypothesized that the oral combination of rivaroxaban and acetylsalicylic acid presents a therapeutic advantage over other treatments. Methods: A prospective longitudinal and non-randomized study of a single center was performed. 59 patients with peripheral arterial disease were included and treated with acetylsalicylic acid + rivaroxaban. Peak systolic velocity, ankle-brachial index and C reactive protein index were evaluated. Results: Significant changes were found at month 1 and 3 of follow-up in maximum systolic velocity, ankle-arm index and C-reactive protein index. The baseline peak systolic velocity (PSV) in the anterior tibial artery had significant differences after one month of treatment (p=0.001) and after 3 months (p=0.001). The baseline PSV in the posterior tibial artery had significant differences compared to the values found at the month of treatment (p=0.001) and 3 months (p=0.001). In the ankle-brachial index a baseline median of 0.790 was found, one month after the treatment of 0.795 (p=0.147) and 3 months after 0.800 (p=0.019). The mean baseline C-reactive protein obtained was 73.142 mg/l, at one month 87.233 mg/l (p=0.001) and at 3 months at 79.009 mg/l (p=0.294) with a standard deviation of 67.18, 74.78 and 69.69 respectively. Conclusions: The combined use of acetylsalicylic acid and rivaroxaban allows a clinical improvement in patients with peripheral arterial disease.